Perancangan Sistem Informasi Pembelajaran Algoritma dan Pemrograman Berbasis Web pada Program Studi Teknik Informatika STMIK ERESHA - Samsudin Samsudin; Indrawan Indrawan; Sri Mulyati (Teknik Informatika Universitas Pamulang, 2020)
This study aims to present web-based algorithm and programming materials in order to increase interest and motivation in studying in the informatics engineering study program, this learning system is made so that all who want to learn algorithms and programming easily get solutions from the material and videos that are available on the web page. And the existence of this web-based learning information system can provide material archive storage and exercises so that there is no more loss of material or exercise files. This application is created using the PHP and MySQL programming languages.